Ab initio computations of zero-field splitting parameters and effective exchange integrals for single-molecule magnets (Mn12- and Mn11Cr-acetate clusters). (4th November 2017) - Sano, Shinsuke; Kawakami, Takashi; Yoshimura, Shohei; Shoji, Mitsuo; Yamanaka, Shusuke; Okumura, Mitsutaka; Nakajima, Takahito; Yamaguchi, Kizashi
Graphical abstract: The zero-field splitting parameters ( D, E ) and effective exchange integrals ( J ) for a Mn12 /Mn11 Cr mixed crystal were evaluated using ab initio molecular orbital (MO) computations based on the hybrid density functional theory (DFT) methods. Abstract: In this study, the zero-field splitting parameters ( D, E ) and effective exchange integrals ( J ) for a Mn12 /Mn11 Cr mixed crystal were evaluated using ab initio molecular orbital (MO) computations based on the hybrid density functional theory (DFT) methods for Mn11 Cr ∗ -acetate cluster (Mn12 and Mn11 Cr mixing). In this study, Mn12 -acetate, Mn11 Cr-acetate, and Mn12− n Cr n -acetate clusters were focused on. The zero-field splitting (ZFS) parameters are obtained by UB3LYP methods, i.e. −0.339 cm −1 (Mn12 -acetate) and −0.351 cm −1 (Mn11 Cr-acetate). The energy barriers were estimated to be 53.7 K and 50.4 K, which showed good agreement with previously reported experimental values of 68.8 K and 56.8 K, respectively. The origin of such anisotropy is assumed to be the eight Mn III ions with d 4 -electrons in their outer ring subunits, where elongated conformation along the axial direction becomes very important and leads to negative D values. The spin networks in these clusters were discussed by using the effective exchange integral sets. The J s value, as estimated by the UB3LYP method revealed that the J 2, J 3, and J 3 ′ interactions played important roles in describing the parallel spin ordering in cubane and ring subunits as well as the antiferromagnetic coupling between two subunits. The other interactions, i.e. J 1, J 1 ′, J 4, and J 4 ′ somewhat disturbed the spin ordering in the Mn12 -acetate cluster. The substitution of Mn IV by Cr III did not change the spin network. However, the total S value changed after the substitution.